Testing The Three Factor Model Of Fama And French: Evidence From An Emerging Market - Achola, Nayema Kevin; Muri, Peter W (European Scientific Journal, ESJ, 2016)
This study tested the three factor model of Fama and French (1993) using the Nairobi Securities Exchange (NSE) data using excess returns of six portfolios sorted by size and Book-to-Market Equity for the three factor model and size and trade concentration ratio for the augmented model. The study used daily stock prices for the period July 2004 to June 2014. Our results show that the predictions of the three factor model hold on NSE especially when the model is adjusted for thin trading. However, the premium is not statistically significant. Further, firms with high trade concentration posted higher returns than firms with low trade concentration during the study period.